Method for improving strength and plasticity of additive manufacturing titanium alloy through Si

By introducing supersaturated Si into the additively manufactured titanium alloy, the solid solution and structure refinement of Si are solved, and the problems of coarse structure and poor strong plasticity of titanium alloy are significantly improved.

CN119457113AActive Publication Date: 2025-02-18HEBEI UNIV OF TECH

Patent Information

Application Number
CN202411729613.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The additive manufacturing titanium alloy has a thick structure and poor plasticity, and traditional methods are difficult to effectively solve through component design.

Method used

By introducing supersaturated Si into the titanium alloy, the high-cooling speed characteristics of additive manufacturing are used to make Si dissolved in the titanium alloy, avoiding the formation of brittle titanium silicon compounds, refine grains and structures, and achieving fine crystal strengthening.

Benefits of technology

Without heat treatment, the tensile strength and elongation of break of titanium alloy are significantly improved, and the strong plasticity matching degree is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457113A_ABST
    Figure CN119457113A_ABST
Patent Text Reader

Abstract

The invention relates to a method for improving the strength and plasticity of an additive manufacturing titanium alloy through Si. The method comprises the following steps: (1) mixing silicon source powder and titanium source powder to obtain mixed powder; (2) taking ball-milling mixing as an example: carrying out ball-milling mixing on the prepared mixed powder under the protection of argon; and (3) the mixed powder obtained after ball milling is subjected to a forming process, and a titanium alloy block is obtained. The forming process is additive manufacturing and comprises a direct laser deposition technology, a laser powder bed melting technology and the like. According to the method, the strength and plasticity of the titanium alloy are greatly improved without heat treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the strength and plasticity of titanium alloys manufactured by additive manufacturing through Si, and belongs to the technical field of metal preparation. Background Art

[0002] Titanium alloys have been widely used in aerospace, chemical engineering, marine engineering, medical equipment and other fields due to their high specific strength, excellent fatigue resistance, outstanding corrosion resistance and oxidation resistance, as well as excellent damage tolerance. Despite these advantages, titanium alloys have low thermal conductivity, high deformation resistance and narrow forging temperature range, which pose major challenges to the manufacture of complex parts. These characteristics may make it difficult to form parts with complex shapes and increase manufacturing costs. Additive manufacturing technology, with its high material utilization rate and forming capabilities that are not limited by part shape and size, not only effectively overcomes these technical bottlenecks, but also achieves lightweight, high performance and low cost of parts.

[0003] Titanium alloy additive manufacturing technology is gradually maturing, but there are still some common problems. In the traditional titanium alloy printing process, coarse columnar crystals will be formed, resulting in anisotropy of mechanical properties, which is not conducive to application. At the same time, the coarse structure is not conducive to obtaining high mechanical properties (fine grain strengthening). The printed titanium alloy structure is mostly coarse martensite, which has high strength but poor plasticity (low elongation). Subsequent heat treatment is required to partially decompose or completely eliminate the martensite to improve plasticity, but this comes at the cost of strength loss, and also increases production processes and costs.

[0004] Taking Ti6Al4V alloy, which is currently the most widely used alloy, as an example, the main solution is to introduce alloying elements to suppress the formation of columnar crystals by strengthening the supercooling of the components, thereby achieving a fine equiaxed crystal structure. These elements include Fe, Co, Cu, Mo, etc. The effectiveness of this method has been verified by a large number of experiments. Si is a eutectic β-stabilizing element, which theoretically also has the effect of eliminating columnar crystals and refining grains. Studies on traditional cast / forged titanium alloys have confirmed that Si easily reacts with titanium to form brittle titanium-silicon compounds, which will lead to a decrease in the plasticity of titanium alloys. Therefore, the introduction of Si is usually avoided in titanium alloys, and even if it is introduced, it is lower than the solubility (0.4 wt%), so the Si content in titanium alloys is lower than this theoretical value. Additively manufactured titanium alloys themselves have the problem of poor plasticity, so Si is not considered to be an effective element to improve the performance of additively manufactured titanium alloys. The key to improving the performance of additively manufactured titanium alloys with Si elements is to ensure that Si exists in the form of solid solution and does not form titanium-silicon compounds. For the problem of printed titanium alloys with martensite structure, there is currently no effective method to solve it through component design except heat treatment and control of printing process. Summary of the invention

[0005] The purpose of the present invention is to provide a method for improving the strength and plasticity of titanium alloys manufactured by additive manufacturing by using Si, in response to the current problems of coarse structure and poor strength and plasticity of titanium alloys manufactured by additive manufacturing. The method introduces supersaturated Si into the titanium alloy without forming brittle titanium-silicon compounds, and uses Si to improve the alloy's component supercooling to achieve the transformation from columnar crystals to fine equiaxed crystals, while refining the lamellar structure to maximize fine grain strengthening; the high cooling rate of additive manufacturing is used to force Si to be dissolved in the titanium alloy without forming brittle titanium-silicon compounds. The present invention achieves a significant improvement in the strength and plasticity of the titanium alloy without heat treatment.

[0006] To achieve the above object, the present invention is implemented through the following technical solutions: A method for improving the strength and plasticity of titanium alloys manufactured by additive manufacturing by Si, comprising the following steps: (1) Preparation of mixed powder The silicon source powder and the titanium source powder are mixed to obtain a mixed powder; The target component mass is calculated by taking the sum of the mass of Si and Ti in the mixed powder as the target component mass, the mass of silicon is 0.4% to 4% of the target component mass, and the remainder is Ti; The silicon source is pure silicon powder, SiO2, SiC or silicon-titanium master alloy (TixSiy); The titanium source is pure titanium or a titanium alloy; the titanium alloy is specifically α titanium alloy, β titanium alloy or α+β titanium alloy; Preferred are Ti6Al4V, TA7 or Ti1023.

[0007] (2) Mechanical mixing of mixed powder Take ball milling as an example: the prepared mixed powder is ball milled under argon protection, and the ball milling parameters are: ball-to-material ratio 2:1-15:1, rotation speed 100-500 rpm, ball milling time 0.5-6 hours; (3) Molding process The mixed powder after ball milling is subjected to a molding process to obtain a titanium alloy block.

[0008] The molding process described is additive manufacturing, including direct laser deposition, laser powder bed fusion technology, etc.

[0009] The direct laser deposition technology includes the following steps: laser power is 600-1500 W, single track width is 1.5-3 mm, track spacing is 0.9-1.8, scanning speed is 5-15 mm / s, and each layer is alternated by 0-90°.

[0010] When using laser powder bed fusion technology, the following steps are included: laser power is 100~500 W, scanning speed is 1000~2000 mm / s, rotation angle between layers is 20~90°, and layer thickness is 0.3~0.8 mm.

[0011] The essential features of the present invention are: Adding silicon to traditional cast / forged titanium alloys can easily form brittle silicides, thereby reducing plasticity, so it is usually avoided. However, silicon is beneficial to high-temperature performance, so a small amount of silicon is added to some high-temperature alloys, that is, below the solid solubility, to ensure that silicon does not form brittle silicides. The microstructure of additively manufactured titanium alloys is mostly coarse columnar crystals and martensite, which leads to significant performance anisotropy and low strength and plasticity. At present, the main method is to increase the supercooling of the molten pool composition by introducing alloying elements such as Fe, B, O, Mo, and Cu, thereby achieving microstructure refinement and improving strength and plasticity. The solubility of Si in titanium is low (0.4 wt%) and it is very easy to form brittle silicides, resulting in plasticity loss, which leads to the introduction of Si into titanium alloys as little as possible, and even if it is introduced, it is controlled below the solid solubility.

[0012] The inventors have found through research that by introducing Si into titanium alloys through additive manufacturing technology, at the high cooling rate of additive manufacturing, Si far exceeding the solubility will also be dissolved in the titanium matrix (more than 3.5 times the solubility in Example 1), which not only avoids the adverse effects of the formation of brittle silicides on plasticity, but also refines the structure and achieves a significant improvement in the strength and plasticity of titanium alloys. Therefore, the essential feature of the present invention is to successfully introduce supersaturated Si into titanium alloys through additive manufacturing technology without forming brittle silicides, thereby achieving a significant improvement in structure refinement and strength and plasticity.

[0013] The beneficial effects of the present invention are: In current technology, it is difficult for additively manufactured Ti6Al4V alloys using other elements as modifiers to simultaneously meet the requirements of tensile strength greater than 1300 MPa and elongation greater than 10%, while the ideal metal structural material maintains good plasticity and toughness while maintaining high strength.

[0014] The present invention can significantly improve the strength of the material without sacrificing the elongation of the material. Taking the most widely used Ti6Al4V alloy as an example, the tensile strength of the titanium alloy printed by the same process as Example 1 is 1110MPa, and the elongation at break is 7.26%, which is comparable to the results reported so far. The tensile strength of the supersaturated Si-enhanced Ti6Al4V alloy prepared by direct laser deposition in Example 1 is increased to 1407MPa, and the elongation at break is increased to 9.61% ( Figure 4 ), and the present invention does not require heat treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the optical microscopic grain image of Example 1 and Ti6Al4V prepared by the same process.

[0016] Figure 2 TEM morphology of Example 1 and Ti6Al4V prepared by the same process.

[0017] Figure 3 This is the energy spectrum element analysis diagram of Example 1.

[0018] Figure 4 The stress-strain curves of Example 1, Example 2 and Ti6Al4V prepared by the same process.

[0019] Figure 5 The following are actual pictures of the titanium alloys of Examples 1 and 2. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with embodiments.

[0021] The Si-enhanced titanium alloy additive manufacturing process of the present invention is as follows Figure 1 As shown. We designed the ball milling of titanium powder and silicon powder, and realized the transformation of columnar crystals to fully equiaxed crystals through the subsequent preparation process, and realized the nano-sizing of martensite and the solid solution strengthening of supersaturated silicon. Thereby improving the mechanical properties of additively manufactured titanium alloys, the present invention provides a method for preparing ultra-high strength and plastic titanium alloys using additive manufacturing processes without post-processing. First, the technical route of the present invention is explained.

[0022] (1) Preparation of mixed powder The silicon source powder and the titanium source powder are mixed to obtain a mixed powder; The target component mass is calculated by taking the sum of the mass of Si and Ti in the mixed powder as the target component mass, the mass of silicon is 0.4% to 4% of the target component mass, and the remainder is Ti; The silicon source is pure silicon powder, SiO2, SiC or silicon-titanium master alloy (TixSiy); The titanium source is pure titanium or a titanium alloy; the titanium alloy is specifically α titanium alloy, β titanium alloy or α+β titanium alloy; Preferred are Ti6Al4V, TA7 or Ti1023.

[0023] (2) Ball milling of mixed powder The prepared mixed powder is ball-milled under argon protection, and the ball-milling parameters are as follows: ball-to-material ratio 2:1-15:1, rotation speed 100-500 rpm, and ball-milling time 0.5-6 hours; (3) Molding process The mixed powder after ball milling is subjected to a molding process to obtain a block titanium alloy.

[0024] The molding process described is additive manufacturing, including direct laser deposition, laser powder bed fusion technology, etc.

[0025] Direct laser deposition technology was used: laser power was 600-1500 W, single track width was 1.5-3 mm, track spacing was 0.9-1.8, scanning speed was 5-15 mm / s, and each layer alternated 0-90°.

[0026] When using laser powder bed fusion technology, the following steps are included: laser power is 100~500 W, scanning speed is 1000~2000mm / s, rotation angle between layers is 20~90°, and layer thickness is 0.3~0.8mm.

[0027] The silicon powder has a purity of 99%, and the Ti6Al4V titanium alloy powder is a conventional commercial alloy powder.

[0028] The present invention is further described below in conjunction with embodiments. Example 1 Weigh 2.5 g silicon powder and 197.5 g Ti6Al4V titanium alloy powder (containing 177.75 g titanium) into a 500 ml stainless steel ball mill jar filled with argon. Use a planetary ball mill at 350 rpm for 2 hours, with a ball-to-material ratio of 2.5:1.

[0029] The mixed powder after ball milling was taken out and the sample was prepared by laser deposition process, with laser power of 900 W, scanning speed of 10 mm / s, alternating 90° between layers, powder feeding speed of 3 g / min, single track width of 2 mm, and track spacing of 1.2 mm. A Si-enhanced Ti6Al4V sample with a length of 80 mm, a width of 30 mm, and a height of 20 mm was obtained. (Among them, the sum of the mass of Si and Ti elements in the alloy is the target component mass, and the mass of silicon is 1.4% of the target component mass;) Example 2 Weigh 1 g silicon powder and 199 g Ti6Al4V titanium alloy powder, place them in a 500 ml stainless steel ball mill, fill with argon, and use a planetary ball mill at 350 rpm for 2 hours, with a ball-to-material ratio of 2.5:1.

[0030] The mixed powder after ball milling was taken out and the sample was prepared by laser deposition process, with laser power of 900 W, scanning speed of 10 mm / s, alternating 90° between layers, powder feeding speed of 3 g / min, single track width of 2 mm, and track spacing of 1.2 mm. A Si-enhanced Ti6Al4V sample with a length of 80 mm, a width of 30 mm, and a height of 20 mm was obtained. The effect was similar to that of Example 1. (Wherein, the sum of the masses of Si and Ti elements of the alloy was taken as the target component mass, and the mass of silicon was 0.56% of the target component mass;) Example 3 Weigh 2.5 g silicon powder and 197.5 g Ti6Al4V titanium alloy powder (containing 177.75 g titanium), place in a 500 ml stainless steel ball mill, and fill with argon. Use a planetary ball mill at 350 rpm for 2 hours, with a ball-to-material ratio of 2.5:1. Take out the mixed powder after ball milling, and use laser powder bed melting technology for sample preparation, with a laser power of 350 W, a scanning speed of 1200 mm / s, a rotation angle of 60° between each layer, and a layer thickness of 0.4 mm. Obtain a Si-enhanced Ti6Al4V sample with a length of 80 mm, a width of 10 mm, and a height of 10 mm. The effect is similar to that of Example 1.

[0031] The optical microscope test results of Ti6Al4V and Si-enhanced Ti6Al4V prepared by additive manufacturing process in Example 1 are as follows: Figure 1 As shown in the figure, the Ti6Al4V alloy presents columnar grains, while the alloy in Example 1 presents fine equiaxed grains, indicating that the addition of Si can inhibit the formation of columnar crystals and achieve the effect of grain refinement, which is one of the reasons for improving the strength and plasticity of titanium alloy at the same time; Figure 2 The transmission electron microscope morphology of nano-martensite in the titanium alloy of Example 1 is shown in FIG. 1 , and the average width of the martensite is refined to about 200 nm, which is another reason for improving both the strength and plasticity of the titanium alloy.

[0032] Figure 3 This is the micro-area energy spectrum of the titanium alloy of Example 1. The results show that Si is evenly distributed in the matrix and no silicide appears, which has the effect of solid solution strengthening.

[0033] The tensile test results of Example 1 and Example 2 are as follows Figure 4As shown (the test is based on GB / T228.1-2021), it can be seen from the figure that compared with the Ti6Al4V alloy prepared by the same process, the strength of Example 1 and Example 2 is significantly improved, and the elongation is also significantly improved. Compared with the sample of Example 1, the Ti6Al4V alloy prepared by the same process has a lower strength than the sample of Example 1 due to the coarse columnar grains and micron-sized martensite. The sample of Example 1 has higher strength and no reduction in elongation due to the synergistic strengthening effect of fine equiaxed crystals and nano-martensite.

[0034] Figure 5 The physical image of the printed sample shows that the sample has high shape stability and good surface quality, which is beneficial for the preparation of complex structural parts.

[0035] The high cooling rate and high thermal gradient inherent in the additive manufacturing process of titanium alloys usually lead to high-density micron-sized martensite, and almost entirely columnar grains, resulting in serious anisotropy of its performance and serious mismatch between strength and plasticity. The preparation of isotropic titanium alloys with both strength and toughness has always been the unremitting pursuit of scientific researchers. The present invention can significantly improve the strength and plasticity of existing additively manufactured titanium alloys. Taking the most typical Ti6Al4V alloy as an example, Example 1 can increase the tensile strength from 1110MPa to 1407MPa, and the elongation from 7.29% to 9.96%. The method of the present invention for improving the strength and plasticity of additively manufactured titanium alloys by supersaturated Si can effectively solve the bottlenecks and problems of columnar crystal growth and strength-plasticity mismatch of additively manufactured titanium alloys, and is expected to be applied in the fields of aerospace and military equipment.

[0036] Matters not covered by the present invention are known technologies.

Claims

1. A method for improving the strength and plasticity of titanium alloy by additive manufacturing using Si, characterized in that the method comprises the following steps: (1) Preparation of mixed powder According to the silicon source powder and titanium source powder are mixed to obtain a mixed powder, The target component mass is calculated by taking the sum of the mass of Si and Ti in the mixed powder as the target component mass, the mass of silicon is 0.4% to 4% of the target component mass, and the remainder is Ti; The silicon source is pure silicon powder, SiO2, SiC or silicon-titanium master alloy; The titanium source is pure titanium or a titanium alloy; the titanium alloy is specifically α titanium alloy, β titanium alloy or α+β titanium alloy; (2) Mechanical mixing of mixed powder Take ball milling as an example: the prepared mixed powder is ball milled under argon protection, and the ball milling parameters are: ball-to-material ratio 2:1-15:1, rotation speed 100-500 rpm, ball milling time 0.5-6 hours; (3) Molding process The mixed powder after ball milling is subjected to a molding process to obtain a titanium alloy block; The molding process described is additive manufacturing.

2. The method for improving the strength and plasticity of titanium alloys by adding Si as claimed in claim 1, characterized in that the titanium alloy is Ti6Al4V, TA7 or Ti1023.

3. The method for improving the strength and plasticity of titanium alloys by additive manufacturing using Si as described in claim 1, characterized in that the molding process is direct laser deposition or laser powder bed melting technology.

4. The method for improving the strength and plasticity of titanium alloys manufactured by additive manufacturing by Si as claimed in claim 1, characterized in that when the direct laser deposition technology is used, the method comprises the following steps: the laser power is 600-1500 W, the single track width is 1.5-3 mm, the track spacing is 0.9-1.8, the scanning speed is 5-15 mm / s, and the layers are alternated by 20-90°; When using laser powder bed fusion technology, the following steps are included: laser power is 100~500 W, scanning speed is 1000~2000 mm / s, rotation angle between layers is 20~90°, and layer thickness is 0.3~0.8 mm.

Citation Information

Patent Citations

  • Ultrahigh-toughness beta titanium alloy and preparation method thereof

    CN114836651A

  • High-strength and high-plasticity Ti-Mo-Al-Nb-Si titanium alloy and preparation method thereof

    CN117778809A

  • Preparation method of ultrahigh-strength plastic TB8G titanium alloy

    CN118256760A

  • Preparation method of isotropic electric arc additive manufacturing titanium alloy with fine congruent-axis beta grains

    CN118951046A

  • HIGH-STRENGTH AND LOW-MODULUS BETA-TYPE Si-CONTAINING TITANIUM ALLOY, PREPARATION METHOD THEREFOR AND USE THEREOF

    US20200056267A1

Cited By

  • Method for preparing high-toughness titanium-based composite material through selective laser melting

    CN121491362A